Working Conditions of Forensic Medicine Specialists and Residents During Pandemic and Lockdown Periods: A Survey Study - Ersoy, Gökhan; Uygul, Elif Sazak; Günbeği, Meltem; Özdemir , Mert Onur; Ergönen, Akça Toprak; Aydın, Berna (The Bulletin of Legal Medicine, 2021)
Objective COVID pandemic has caused changes in the work and daily life of forensic medicine physicians. The present study examines the pandemic's risks on forensic medicine physicians' health, changes in forensic medicine service, and physicians' opinions about the non-forensic medical duties.  Methods: We applied a survey with 31 questions to 220 physicians, including specialist and assistant positions in the field of forensic medicine. We surveyed changes in daily and working life conditions.Results: 52% of physicians stated that their occupation increased their worries about COVID-19. The rate of the participants, who changed their accommodation sites during the pandemic, was 19%. They also declared a diminishing number of weekly working days. Of 154 people performing a forensic clinical examination, 87% stated that the number of cases decreased, and 23% specified that family violence cases increased. One hundred twenty-eight physicians (58%) were redeployed to non-forensic medicine services. COVID examination room and COVID clinic were the most assigned departments (60 and 26 participants, respectively). The rate of those who did not consider themselves sufficient for these tasks was 27%.Conclusion: The Lockdown period has reduced the workload of forensic medicine for a while. In this period, forensic medicine physicians have highly employed in COVID services, especially residents. As there were notable changes in examination and living environments, the rate of feeling inadequate for non-forensic medical duties has approached one fifth. Structuring postgraduate or on-site education of the physicians will keep these skills alive.
Keywords: Redeployment, Competency, COVID-19, Medical Education, Personal Protective Equipment (PPE), Autopsy